Mental Health Across the Atrial Fibrillation Continuum: Mechanisms, Outcomes, and Clinical Implications - Aikaterini-Eleftheria Karanikola; Dimitrios Tsiachris; Georgia Balta; Panagiotis Alexandrou; Athanasios Dedousis; Fotis Tatakis; Michail Botis; Athanasios Kordalis; Konstantinos Tsioufis (Life, 2026)
Atrial fibrillation (AF) is the most common supraventricular arrhythmia in adults, with a rising prevalence and a significant impact on quality of life and major cardiovascular outcomes. While atrial structural and electrical remodeling have long been central to AF pathophysiology, increasing evidence highlights the importance of psychological and mental health factors throughout the disease course. Depression, anxiety, and chronic stress are highly prevalent among individuals with AF and are associated with increased symptom burden, impaired quality of life (QoL), reduced treatment adherence, lower utilization of evidence-based therapies, and adverse clinical outcomes. Conversely, the diagnosis of AF itself may contribute to psychological distress, highlighting a complex bidirectional relationship between mental health and AF. This review summarizes current evidence on this interplay, with a focus on underlying mechanisms, including autonomic dysfunction and inflammation. Furthermore, the influence of mental health on outcomes and therapeutic strategies, and the clinical relevance of a multidisciplinary approach in contemporary AF management, are also examined.